Commensal Bacterial Endocytosis in Epithelial Cells Is Dependent on Myosin Light Chain Kinase–Activated Brush Border Fanning by Interferon-γ - Wu, Li-Ling (American Society for Investigative Pathology, 2014)
Abnormal bacterial adherence and internalization in enterocytes have been documented in Crohn disease, celiac disease, surgical stress, and intestinal obstruction and are associated with low-level interferon (IFN)-γ production. How commensals gain access to epithelial soma through densely packed microvilli rooted on the terminal web (TW) remains unclear. We investigated molecular and ultrastructural mechanisms of bacterial endocytosis, focusing on regulatory roles of IFN-γ and myosin light chain kinase (MLCK) in TW myosin phosphorylation and brush border fanning. Mouse intestines were sham operated on or obstructed for 6 hours by loop ligation with intraluminally administered ML-7 (a MLCK inhibitor) or Y27632 (a Rho-associated kinase inhibitor). After intestinal obstruction, epithelial endocytosis and extraintestinal translocation of bacteria were observed in the absence of tight junctional damage. Enhanced TW myosin light chain phosphorylation, arc formation, and brush border fanning coincided with intermicrovillous bacterial penetration, which were inhibited by ML-7 and neutralizing anti–IFN-γ but not Y27632. The phenomena were not seen in mice genetically deficient for long MLCK-210 or IFN-γ. Stimulation of human Caco-2BBe cells with IFN-γ caused MLCK-dependent TW arc formation and brush border fanning, which preceded caveolin-mediated bacterial internalization through cholesterol-rich lipid rafts. In conclusion, epithelial MLCK-activated brush border fanning by IFN-γ promotes adherence and internalization of normally noninvasive enteric bacteria. Transcytotic commensal penetration may contribute to initiation or relapse of chronic inflammation.